Indigenous hillstream fishing practices in Telangana State, India - Kante Krishna Prasad
The present study deals with the traditional knowledge of various fishing techniques and practices of tribes and local fishermen in the Telangana State. Field surveys were carried out across the state during the period of 2013 to 2021 and we have documented all hillstream fishing activities by tribes and local fishermen. All hillstream fishing activities were categorized into three categories based on fish-catching methods: poisoning, trapping, and traumatizing. During the study period, we documented a total of 16 piscicidal plant species used by various tribes around the state. Bamboo traps, casting nets, constructing pseudo-littoral zones, hooks, long cloth method, pot/dish trap and stream diversion approaches were all listed as trapping methods. The technique of traumatizing involves hitting with a stone. These are all techniques that facilitate future researchers, fishermen, and aquarium traders to understand the various fishing methods used in the stream water, as well as to catch live fish for scientific studies, aquarium trades, and sustainable use of natural resources. Other recent trends discussed include high-voltage electric fishing, the use of explosives, poisoning with commercial pesticides, and bleaching powder (Ca(OCl)2) to catch hillstream fish by local fishermen in the state. Indigenous fishing practices can help to establish eco-friendly methods for aquarium fish trading, research, providing a source of income for unemployed youth in remote areas, and maintaining a sustainable utilization of natural resources.